Penerapan Model Kooperatif Learning Tipe Jigsaw dalam Meningkatkan Aktivitas Belajar Matematika Siswa Kelas IX 2022/2023 MTsN 1 Kota Padang - Rusyda Masyhudi (Journal on Education, 2023)
Lack of student activity in learning and student enthusiasm and the atmosphere and conditions in class affect the learning process in the classroom. Teachers need to determine the right method because it has an impact on the success of learning. Therefore, teachers and students need an effective and innovative learning model. The learning model used in this study is a jigsaw cooperative learning model. This study aims to increase learning activities in mathematics for Class IX.1 MTsN 1 Padang City students in the 2022/2023 academic year through the application of jigsaw type cooperative learning model. This research is a Classroom Action Research (PTK) which was carried out in two cycles. The data collection technique used was participatory observation and documentation while the data analysis technique used was quantitative descriptive data analysis with percentages. The results of this study indicate that the application of the Jigsaw Cooperative Learning Model can increase learning activities in Mathematics for Class IX.1 MTsN 1 Padang City in the 2022/2023 Academic Year. The average percentage of learning activities in Mathematics subject increased 16.03% from the first cycle of 60.64% to 76.67% in the second cycle. An increase in learning activities in mathematics is also indicated by an increase in the number of indicators that meet the minimum criteria of 75%.